Do Speaker's emotions influence their language production? Studying the influence of disgust and amusement on alignment in interactive reference. (March 2020) - Out, Charlotte; Goudbeek, Martijn; Krahmer, Emiel
Abstract: The influence of emotion on the early stages of spoken language production such as content selection has received little scholarly attention. During content selection in dialogue, speakers often take the utterances of their dialogue partners into account. For example, while speakers generally prefer to use color in their descriptions, they start to use dispreferred attributes such as orientation and size more when they are primed by a prerecorded partner using these dispreferred attributes (Goudbeek and Krahmer, 2012). The current study assessed the role of amusement and disgust in this process of conceptual alignment, while simultaneously replicating this earlier finding in a more realistic setting. Three types of alignment were analyzed: alignment of dispreferred properties (with or without additional properties), alignment of overspecified descriptions (both used by G&K), and alignment of dispreferred properties only. The results generalize the findings by Goudbeek and Krahmer (2012) to a more naturalistic dialogue setting: partners indeed align with each other's attributes in the choice of their referring expressions. The effects of emotion were generally limited, but disgusted speakers do tend to align more to the dispreferred attributes (e.g., size) used by their conversation partner than amused speakers. Our findings highlight the robustness of alignment in referring expressions produced in interactive settings, and suggest that emotional state can have an impact on this process. Highlights: Speakers often adapt their references to their dialogue partner. We study the alignment process in dialogue, building on earlier studies. We ask whether emotions influence referential adaptation in dialogue. Our results suggest that disgusted speakers align more than amused ones. Our results replicate earlier alignment finding in a more naturalistic setting.